Communication, cinema, development from morosity to hope - Roberge, Gaston 1935-2020. (New Delhi Manohar, 1998)
Collection of articles published in various newspapers; with reference to India.
Includes bibliographical references and index.
CMC-2902 donated by Prof. Arminda V. Santiago.
Keywords: Motion pictures -- India; Motion pictures -- Social aspects -- India